2021
DOI: 10.52953/shes9692
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz band communications as a new frontier for drone networks

Abstract: Terahertz band (0.1-10 THz) communications is one of the candidates for 6G systems due to intrinsic massive bandwidth and data rate support. Having demonstrated the significant potential of THz band at various atmospheric altitudes, in this article, we discuss the prospects of THz communications for drone networks, more specifically, for Drone Sensor Networks (DSNs). For 6G non-terrestrial communication scenarios, drones will not only serve as on-demand base-stations, as supporting alternatives or backhauls fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 82 publications
0
2
0
Order By: Relevance
“…A few recent studies have shown the massive potential of employing the THz band for aerial communications with a substantial performance improvement as compared to the THz communications at sea level. In [13], open research directions for drone networks over the THz band are presented, highlighting issues in channel estimation, physical layer, Ultra-Massive Multiple Input Multiple Output (UM-MIMO), and Mobile Edge Computing (MEC), to name a few. In [4], an extensive analysis of THz band communications of four practical aerial vehicle scenarios is provided for drones, jet planes, high altitude UAVs, and satellites at various practical altitudes, transmission distances, zenith angles, weather pro iles, and fading conditions of Multipath (MP) fading and Beam Misalignment (BM) fading.…”
Section: Total Path Lossmentioning
confidence: 99%
See 1 more Smart Citation
“…A few recent studies have shown the massive potential of employing the THz band for aerial communications with a substantial performance improvement as compared to the THz communications at sea level. In [13], open research directions for drone networks over the THz band are presented, highlighting issues in channel estimation, physical layer, Ultra-Massive Multiple Input Multiple Output (UM-MIMO), and Mobile Edge Computing (MEC), to name a few. In [4], an extensive analysis of THz band communications of four practical aerial vehicle scenarios is provided for drones, jet planes, high altitude UAVs, and satellites at various practical altitudes, transmission distances, zenith angles, weather pro iles, and fading conditions of Multipath (MP) fading and Beam Misalignment (BM) fading.…”
Section: Total Path Lossmentioning
confidence: 99%
“…A recent study in [12] has considered THz band (0.1-10) THz wireless communications for new deep space explorations e.g., for Mars-space THz links. Spectrum management will place an important role in regard to the interference issue in the THz band [13]. A massive THz band can be suf iced for the challenge of spectrum scarcity by allocating sub-bands to individual users, hence, mitigating the interference [14,15].…”
Section: Introductionmentioning
confidence: 99%